Engendering liminality: The experience of re-enchantment in wild woman workshops. (September 2019) - Plancke, Carine
According to Paul Heelas, new spiritualities radicalize the expressivist strand in modernity and, hence, not only affirm modern values but also react against them. In particular, they challenge the 'bounded self' as foundational for the modern being and progress. Charles Taylor, in discussing the emergence in modern times of 'the buffered self', points to three important changes: disenchantment, the loss of the complementary play between structure and anti-structure, and the replacement of the idea of cosmos with that of a neutral, mechanical universe. This article, through a detailed ethnographic study, explores how these changes are temporally counteracted in spiritual women workshops in North-West Europe focused on the trope of the 'wild woman'. Moreover, it shows that these retreats bring into being ritual spaces of liminality, which have the potential to engender experiences of re-enchantment and/or give a new sense of interpersonal and cosmic connection.